Avaliação da microaeração em reator UASB piloto para remoção do sulfeto de hidrogênio produzido no tratamento de esgoto doméstico - Iacy Maria Pereira de Castro (2017)
Influent containing sulphur are particularly undesirable to anaerobic process, especially regarding final products, such as treated effluent and biogas. Problems associated to formation and release of hydrogen sulphide are related to characteristics such as unpleasant odour, corrosivity and toxicity. Studies have demonstrated that small amounts of air/O2 introduction in liquid phase may provide removal of dissolved hydrogen sulphide present in biogas and also dissolved sulphide oxidation potential. Therefore, this research consisted of the evaluation of microaeration techinique performed in the digestion zone of an UASB reactor treating domestic wastewater, aiming to control hydrogen sulphide in both liquid and gas (biogas) phases. The set up comprised of two pilot-scale UASB reactors, including a conventional and a modified UASB reactor operating under microaeration conditions. The research was developed in three phases. Air was introduced 3 m from the bottom of the reactor during phases I and II with the flow of 20 mL.min-1 and 30 mL.min-1 under 7 h and 5 h of HRT conditions, respectively. On phase III, 30 mL.min-1 of air was dosed 1 m from the bottom of the reactor, complying to phase I operational conditions. Results related to microaerobic UASB reactor showed that hydrogen sulphide concentration of biogas were bellow 70 ppmv during phase I, achieving 98% removal efficiency. Through phases II and III, removal efficiences were 95,7% and 94%, respectively. Hydrodynamic variance of the reactor and air aplication height did not decreased H2S removal efficiency regarding biogas. However, dissolved sulphide removal was not observed. The range of methane concentration in biogas of microaerated reactor was 50-55%v/v phase I, 43-55%v/v phase II and 37-45%v/v phase III, bellow methane concentration of anaerobic reactor biogas. Methane dilution was, mainly, influenced by nitrogen present in atmospheric air and dissolved in raw sewage. Organic matter removal efficiency of UASB reactor was not enhanced by microaeration, once removal percentages were about 50 to 70%. Dosed air did not affect specific methanogenic activity (SMA of 0,19 gCODCH4.gVSS-1) and microbial community similarity was not expressively modified. Therefore, air limited introduction in UASB reactor digestion zone was shown an efficient method to remove hydrogen sulphide from gas phase. However, further investigations are still needed regarding dissolved sulphide oxidation since its removal was not observed in the microaerobic reactor.